2004
DOI: 10.1023/b:qure.0000018472.46236.05
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life associated with chronic conditions in eight countries: Results from the International Quality of Life Assessment (IQOLA) Project

Abstract: Arthritis has the highest HRQL impact in the general population of the countries studied due to the combination of a high deviation score on physical scales and a high frequency. Impact of chronic conditions on HRQL was similar roughly across countries, despite important variation in prevalence. The use of HRQL measures such as the SF-36 should be useful to better characterize the global burden of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
482
6
54

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 676 publications
(588 citation statements)
references
References 38 publications
46
482
6
54
Order By: Relevance
“…Postoperative quality of life was assessed by the validated psychometric questionnaire SF-36, which is based on the American short-form-36 health survey [36,37] and has been psychometrically validated [1,5,10]. As the SF-36 score considers 36 items in eight different scales of subjective physical and mental health as well as social and emotional aspects, it is generally considered to reliably assess disease-related quality of life.…”
Section: Oncological Outcomementioning
confidence: 99%
“…Postoperative quality of life was assessed by the validated psychometric questionnaire SF-36, which is based on the American short-form-36 health survey [36,37] and has been psychometrically validated [1,5,10]. As the SF-36 score considers 36 items in eight different scales of subjective physical and mental health as well as social and emotional aspects, it is generally considered to reliably assess disease-related quality of life.…”
Section: Oncological Outcomementioning
confidence: 99%
“…Heart failure considerably affects physical, psychological and social functions of the individual, often making normal daily life activity difficult [2][3][4]. Due to the frequent hospital admission, the costs for HF treatment is substantial and it is expected to rise [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that chronically ill patients have reduced health-related quality of life (HRQL) and are relatively more at risk for mental health problems than those without a chronic disease [1][2][3][4][5][6]. The combination of a distressing chronic disease with other stressful life events might increase this risk.…”
Section: Introductionmentioning
confidence: 99%